A Life of Gwendolyn Brooks - Kent, George E., 1920-1982 (Book collections on Project MUSE., 1990)
This is the first full-scale biography of Gwendolyn Brooks, one of America's major poets. George E. Kent, a longtime friend and literary associate of the poet in Chicago, was given exclusive access to Brooks' early notebooks, which she kept from the age of seven. Kent also interviewed Brooks, her mother, and other family members in Chicago and elsewhere. He scoured records and correspondence with her publishers, editors, and agent. He participated in the poet's literary enterprises and in her wide circle of literary and family friends. The study reveals intimate acquaintance with the Harlem Re.